Effect of opposition on the handball jump shot - Gutierrez-Davila, M.; Garcia, P. L.; Parraga Montilla, J.; Rojas Ruiz, F. J. (Journal of Human Movement Studies, 2006)
The aim of this study was to analyse the adjustments in technique made by a handball player when shooting against an Opponent. The protocol used to present the Opponent was based on a study of the most common defensive actions developed during the 2003 World Handball Championship in Portugal. Two shots were analysed, with and without Opposition, by handball players from teams playing in the Spanish "B Division of Honour" and specialists in making distance shots. The analysis of the handball Jump shot technique was made by three-dimensional (3D) photogrammetrics. The action was filmed with two video cameras (Panasonic S-VHS NV-MS4) at fifty Images per second and synchronised in time through an electronic slide. Statistically significant differences (p<0.001) were found only in the displacement time (the time of the run prior to the shot), T DISPLACEMENT, which was less with Opposition, and in the horizontal component of velocity at the end of the displacement phase (the player's run before the last touch down in order to jump) (V XY-CG 12), which was greater without Opposition (p><0.05). The lack of statistical significance in the other factors analysed results from the ability of the shooter to overcome the Opponent in the previous run.